Genetic parameters of growth traits in Cuban Zebu cattle - Guill?n Trujillo, A.; Guerra Iglesias, D.; ?vila Serrano, N.; Gonz?lez-Pe?a, Dianelys; Palacios, A.; de Luna, R.; Espinoza, J. L. (Cuban Journal of Agricultural Science, 2011)
In order to estimate (co)variance components and genetic parameters of weaning weight, at seven months of age (WW), and of final weight, at 18 months (FW), a sample was used from 67 373 records of WW and 7 990 records of FW of Cuban Zebu breed animals. They were born between 1988 and 2006, in five genetic centers of the country. The statistical model for WW included the effects of the group of contemporaries (herd?year?trimester-sex, weaning weight as linear covariable and the age of the mother as linear and quadratic), the random effect of the animal, the maternal random effect, the permanent environment effect and the error. The model for FW included the group of contemporariess (herd-year-four-month period), the animal effect and that of the permanent environment. The variance components, estimated through animal model for the direct effect of WW by univariate and bivariate analysis, were similar and did not tend to change significantly the magnitude of the heritability for the direct (0.06 vs. 0.08) and maternal effects (0.06 ? 0.01 vs. 0.05 ? 0.01). However, for the FW, the variance components for the direct effect had important changes. As a result, the h2 was higher when using the bivariate model (0.26 ? 0.05) than when applying the univariate (0.16 ? 0.03). The genetic correlation between the direct and the maternal effect for the weaning weight reached a value of -0.37 ? 0.08 in the univariate analysis, and of -0.21 ? 0.07 in the bivariate. It was concluded that the utilization of an animal model, considering simultaneously weaning weight and final weight, increased the efficiency in the selection of this latter character. Key words: Cuban Zebu cattle, variance components, genetic parameters, growth.